Foaming of Bio-Based PLA/PBS/PBAT Ternary Blends with Added Nanohydroxyapatite Using Supercritical CO2: Effect of Operating Strategies on Cell Structure - Pei-Hua Chen; Chin-Wen Chen; Tzu-Hsien Chan; Hsin-Ying Lin; Ke-Ling Tuan; Chie-Shaan Su; Jung-Chin Tsai; Feng-Huei Lin (Molecules)
This study explored the innovative foaming behavior of a novel biodegradable polymer blend consisting of polylactic acid/poly(butylene succinate)/poly(butylene adipate-co-terephthalate) (PLA/PBS/PBAT) enhanced with nanohydroxyapatite (nHA), using supercritical carbon dioxide (SCCO2) as an environmentally friendly physical foaming agent. The aim was to investigate the effects of various foaming strategies on the resulting cell structure, aiming for potential applications in tissue engineering. Eight foaming strategies were examined, starting with a basic saturation process at high temperature and pressure, followed by rapid decompression to ambient conditions, referred to as the (1T-1P) strategy. Intermediate temperature and pressure variations were introduced before the final decompression to evaluate the impact of operating parameters further. These strategies included intermediate-temperature cooling (2T-1P), intermediate-temperature cooling with rapid intermediate decompression (2T-2P), and intermediate-temperature cooling with gradual intermediate decompression (2T-2P, stepwise ΔP). SEM imaging revealed that the (2T-2P, stepwise ΔP) strategy produced a bimodal cell structure featuring small cells ranging from 105 to 164 μm and large cells between 476 and 889 μm. This study demonstrated that cell size was influenced by the regulation of intermediate pressure reduction and the change in intermediate temperature. The results were interpreted based on classical nucleation theory, the gas solubility principle, and the effect of polymer melt strength. Foaming results of average cell size, cell density, expansion ratio, porosity, and opening cell content are reported. The hydrophilicity of various foamed polymer blends was evaluated by measuring the water contact angle. Typical compressive stress–strain curves obtained using DMA showed a consistent trend reflecting the effect of foam stiffness.